STRATEGI PENGEMBANGAN AGRIBISNIS STRAWBERY (Fragaria Vesca) DI DESA BONTO TALLASA KECAMATAN ULU ERE KABUPATEN BANTAENG - Sahlan Sahlan; Sri Wahyuni (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2019)
ABSTRACT Agricultural development in Bantaeng directed to create an advanced agriculture and resilient, able to increase the yield and quality of production, increase farmers' income and living standards, expanding business opportunities and employment as well as filling and expanding the market. While the use of external inputs - massive and exaggerated to increase the yield and quality of production. The study aims to determine how the Agribusiness Development Strategy Bonto Tallasa Strawbery in Ulu Ere District of Bantaeng. Informants in this study is the unit of analysis (strawberries agribusiness development activities). The informants in this study were obtained intentionally which amounted to 8 people, 4 farmers, 2 Department of Agriculture (Extension) and 2 merchants suspected of knowing about the strawberry agribusiness development in Bonto Tallasa Ulu Ere District of Bantaeng. The results of this study indicate strawberry agribusiness development strategy are: 1. Improve the quantity to meet market demand. Utilizing existing facilities to develop new technologies. 2. Utilizing the experience of farmers and the potential of nature to improve the quality and quantity of the product in order to gain profit increased or high. 3. To collaborate with the government to obtain quality seeds. 4.Memberikan to improve institutional socialization in the application to overcome pests and diseases. 5. Maintaining quality of fruit to deal with competitiveness. 6. Improving understanding of farmers in processing products to meet safety standards and consumer products industries. 7. Utilizing the experience of farmers to cope with erratic weather changes. 8. Provide training to farmers on cultivation of strawberries products to meet the standards of consumer products and avoid competitiveness. 9. Increase the role of the institution to meet the industry. Keywords : Strategy, Agribusiness Development, Strawberry ABSTRAK Pengembangan pertanian di Kabupaten Bantaeng di arahkan untuk menciptakan pertanian yang maju dan tangguh, mampu meningkatkan hasil dan mutu produksi, meningkatkan pendapatan dan taraf hidup petani, memperluas kesempatan berusaha dan menyediakan lapangan kerja serta mengisi dan memperluas pasar. Sementara ini penggunaan input luar secara besar – besaran dan berlebihan untuk meningkatkan hasil dan mutu produksi. Penelitian ini bertujuan untuk mengetahui bagaimana Strategi Pengembangan Agribisnis Strawbery di Desa Bonto Tallasa Kecamatan Ulu Ere Kabupaten Bantaeng. Informan dalam penelitian ini adalah unit analisis (kegiatan pengembangan agribisnis strawbery). Adapun informan dalam penelitian ini yang di peroleh secara sengaja yaitu berjumlah 8 orang, 4 orang petani, 2 Dinas Pertanian (Penyuluh) dan 2 orang pedagang yang diduga mengetahui tentang pengembangan agribisnis strawberry di Desa Bonto Tallasa Kecamatan Ulu Ere Kabupaten Bantaeng. Hasil penelitian ini menunjukkan strategi pengembangan agribisnis strawberry antara lain: 1. Meningkatkan kuantitas untuk memenuhi permintaan pasar. Memanfaatkan sarana yang ada untuk mengembangkan teknologi baru. 2. Memanfaatkan pengalaman petani dan potensi alam untuk meningkatkan kualitas dan kuantitas produk agar mendapatkan laba yang meningkat atau tinggi. 3. Menjalin kerjasama dengan pemerintah untuk memperoleh bibit unggul. 4. Memberikan sosialisasi untuk meningkatkan kelembagaan dalam penerapan untuk menanggulangi hama dan penyakit. 5. Mempertahankan kualitas buah untuk menghadapi daya saing. 6. Meningkatkan pemahaman petani dalam mengolah produk agar mampu memenuhi standar produk konsumen dan industri. 7. Memanfaatkan pengalaman petani untuk mengatasi perubahan cuaca yang tidak menentu. 8. Memberikan pelatihan kepada petani tentang pengolahan produk strawbery untuk memenuhi standar produk konsumen dan menghindari daya saing. 9. Meningkatkan peran lembaga untuk memenuhi industri. Kata kunci : Strategi, Pengembangan Agribisnis, Strawberry.